Community Participation in Village Deliberations: Examining the Dynamics of Influencing Factors - Anggara, Reksi; Pribadi, Ulung (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Community participation in village meetings is essential because it spearheads village development. While the importance of village meetings is widely recognized, the main challenge faced is the low level of participation. Many villages need help attracting the interest and involvement of residents. This study aims to analyze the factors influencing community participation in village deliberation using quantitative methods with the Smart PLS4 analysis tool. This research presents the results of an empirical survey of the people of Sijuk Village, Belitung Regency, Indonesia, as it is considered a typical representation and reflects the general characteristics of villages in the region. The internal and external factors to be tested include education, awareness, information, involvement in community organizations, and village social and institutional structures. The results state that education, awareness, and information variables significantly positively affect community participation. Meanwhile, the variables of involvement in community organizations and the social and institutional structure of the village have no effect. The government and related parties can design policies and programs to increase education, community awareness of village problems, and access to information to motivate active participation in village meetings. This study concludes that this research provides a considerable theoretical contribution, especially in understanding the factors influencing community participation in village meetings.